PENGARUH PROFITABILITAS, LIKUIDITAS DAN KEBIJAKAN UTANG TERHADAP NILAI PERUSAHAAN - Avivaksita (Journal of Accounting and Management, 2025)
The purpose of this study is to obtain empirical evidence on the effect of profitability, liquidity and debt policy on firm value. This study uses a population of food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2020-2023. Then the sampling method used purposive sampling. Data collection techniques by means of documentation and the type of data used is secondary data. Data analysis uses descriptive statistics, model selection tests, classical assumption tests and hypothesis tests. The results of the study revealed that the profitability variable with the Gross Profit Margin (GPM) indicator has a significant effect on firm value, while profitability with the OPM, NPM, ROA and ROE indicators does not affect firm value. Furthermore, the liquidity variable with the Current Ratio, Cash Ratio and Quick Ratio indicators does not affect firm value. The debt policy variable with the DAR, DER indicators does not affect firm value.